Distributive/integrative negotiation strategies in cross-cultural contexts: a comparative study of the USA and Italy - Benetti, Sara; Caputo, Andrea; Ogliastri, Enrique (Cambridge University Press, 2021)
Integrative and distributive negotiation strategies are a key paradigm of practice,teaching,and research. Are these US-formulated negotiation prototypes valid in the rest of the world? Adopting a cross-cultural view,we analyze a sample of 214 foreigners who detailed the negotiation behavior they faced in Italy (134) and in the United States (80). Implementing latent class analysis,we identify three clusters of negotiation prototypes. Our findings show how the Country is a predictor for cluster membership,and peculiar cultural traits of the two groups contribute to explain the differences in negotiation strategies. Three prototypes emerged: a typically distributive,an emotional integrative (mostly Italian),and an impersonal integrative (mostly American). Results show how the handling of emotions is a crucial part of the interaction for Italian negotiators,regardless of their orientation toward negotiation strategies,implying a cultural influence toward handling emotions in negotiations. © Cambridge University Press and Australian and New Zealand Academy of Management 2021. This is an Open Access article,distributed under the terms of the Creative Commons Attribution licence (http://creativecommons.org/licenses/by/4.0/),which permits unrestricted re-use,distribution,and reproduction in any medium,provided the original work is properly cited.
Keywords: Culture; Integrative negotiations; Italy; Latent class analysis; Negotiation prototypes; USA; ODS 11 - Ciudades y comunidades sostenibles